1999
DOI: 10.1046/j.1464-5491.1999.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging techniques demonstrate soft tissue damage in the diabetic foot

Abstract: Changes in MT activity reflect qualitative structural changes which this study reveals are extensive in the diabetic neuropathic foot. Fibrotic atrophy of the plantar fat pad may affect its ability to dissipate the increased weight-bearing forces associated with diabetic neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
50
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 14 publications
4
50
0
Order By: Relevance
“…This clearly indicates that determination of muscle mass reflects motor function. In healthy subjects, r values between muscle strength and total muscle volume exceeded 0.85, a slightly closer relation than the one between muscle cross-sectional area and muscle strength (4).…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…This clearly indicates that determination of muscle mass reflects motor function. In healthy subjects, r values between muscle strength and total muscle volume exceeded 0.85, a slightly closer relation than the one between muscle cross-sectional area and muscle strength (4).…”
mentioning
confidence: 65%
“…In a series of experiments in long-term diabetic patients, we have observed that muscle weakness in the lowerleg muscles occurs to a substantial degree in chronic neuropathic patients, closely related to muscle atrophy, whereas nonneuropathic patients have normal muscle strength and striated muscle mass (3). In the more distally situated intrinsic foot muscles, Brash et al (4) observed atrophy in neuropathic diabetic patients using a specific magnetic resonance imaging (MRI) contrast sequence; however, the atrophy was not quantified. Since diabetic polyneuropathy shows a centripetal pattern of progression, quantification of the more distally situated foot muscles could possibly serve as an early marker for motor dysfunction in diabetic neuropathy.…”
mentioning
confidence: 96%
“…These injuries cause stiffening of the plantar fat pad, which normally cushions the repeated pressures during ambulation. Brash et al (23) found nonspecific fibrosis of the plantar fat pad in diabetic patients with neuropathy. They hypothesized that the factors responsible for the maintenance of normal fat pad include neurological, vascular, and hormonal influences.…”
Section: Discussionmentioning
confidence: 99%
“…The weighted kappa was 0.94, which shows very good intraobserver agreement (13). Remarkable degrees of intrinsic muscle atrophy have been observed in patients with long-standing diabetes and peripheral neuropathy, and were suggested in previous studies to play a significant role in altered gait biomechanics (7,10,11). In those studies, intrinsic muscle atrophy was assessed quantitatively with the use of special MRI sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its multiplanar imaging capability and inherent superiority in tissue contrast, magnetic resonance imaging (MRI) is increasingly being used as a tool to assess structural pathology in the foot or lower leg of diabetic patients with peripheral neuropathy (5,(7)(8)(9)(10)(11). These assessments are considered important for improving our understanding of the relationship between structure and function in the foot and the pathogenesis of foot ulceration.…”
mentioning
confidence: 99%